Peran Ma’had Al-Zaytun dalam Pemenuhan Hak Asasi Manusia Berdasarkan Undang-Undang Nomor 39 Tahun 1999 dan Maqasid Syariah - Robby Husein; Abdur Rahim; M. Isa Asyrofuddin (Pusat Riset dan Inovasi Nasional, 2025)
Human Rights (HAM) are fundamental rights that must be protected by both the state and society. In Islam, human rights are divine in nature, emphasizing justice and equality. Ma’had Al-Zaytun plays a vital role in instilling these values through an educational system aligned with Law No. 39 of 1999 on Human Rights. This study is important to explore the synergy between religion and law in fulfilling human rights. The purpose of this research is to identify the role of Ma’had Al-Zaytun in promoting human rights based on Law No. 39 of 1999 and the principles of Maqasid Shariah. The study uses a descriptive approach with a literature study method. Primary data are obtained from Law No. 39 of 1999 and Jasser Auda’s book Maqasid al-Shariah as Philosophy of Islamic Law: A Systems Approach, while secondary data are collected from journals, theses, dissertations, documents, regulations, and previous research related to the topic. The findings show that Ma’had Al-Zaytun plays a significant role in fulfilling human rights from both the perspective of Law No. 39 of 1999 and Maqasid Shariah. According to the law, Ma’had Al-Zaytun integrates Islamic values and human rights principles into its educational system and daily activities. The rights to life, welfare, religious freedom, education, and respect for others are implemented in daily practice. Meanwhile, from the perspective of Maqasid Shariah, Ma’had Al-Zaytun successfully harmonizes Islamic objectives with human rights principles by ensuring religious freedom, protecting human dignity, and encouraging freedom of thought.